2015
DOI: 10.1016/j.ijcha.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for the study of postnatal cardiac hypertrophy

Abstract: The main objective of this study was to create a postnatal model for cardiac hypertrophy (CH), in order to explain the mechanisms that are present in childhood cardiac hypertrophy. Five days after implantation, intraperitoneal (IP) isoproterenol (ISO) was injected for 7 days to pregnant female mice. The fetuses were obtained at 15, 17 and 19 dpc from both groups, also newborns (NB), neonates (7–15 days) and young adults (6 weeks of age). Histopathological exams were done on the hearts. Immunohistochemistry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Our result demonstrated that in response to cocaine concentrations of 10 µg/mL H9c2 cardiomyocytes underwent enhanced loss of cellular compaction and cell-cell integrity, common features of post-natal cardiac hypertrophy while doses of 1 µg/mL, appeared to cause increased cell polarity [ 29 ]. Studies performed by Badisa et al [ 24 ] suggested that the cell types examined are more inclined to withstand greater cocaine concertation, however, the present investigation indicates cardiomyocytes are more sensitive to higher cocaine concentration exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Our result demonstrated that in response to cocaine concentrations of 10 µg/mL H9c2 cardiomyocytes underwent enhanced loss of cellular compaction and cell-cell integrity, common features of post-natal cardiac hypertrophy while doses of 1 µg/mL, appeared to cause increased cell polarity [ 29 ]. Studies performed by Badisa et al [ 24 ] suggested that the cell types examined are more inclined to withstand greater cocaine concertation, however, the present investigation indicates cardiomyocytes are more sensitive to higher cocaine concentration exposures.…”
Section: Discussionmentioning
confidence: 99%
“…After 96 h from the LAD occlusion or sham operation, the anesthetized animals and the collected hearts were weighed. Heart weight to body weight ratio (HW/BW; mg/g), a common and simple indicator of cardiac hypertrophy (Chiu et al, 2001; Sugden et al, 2008; Del Olmo-Turrubiarte et al, 2015) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Altered expression of acta2 and myh6 , myh7 transcripts, whose impairment is associated to cardiomyocyte cell enlargement in the adult heart 37 , 45 , was found after 1.0 µM ATO exposure. In the mouse ventricle, β-MHC, coded by myh7 , is the predominant isoform in the developing heart, then replaced by α-MHC, coded by myh6 , after birth.…”
Section: Discussionmentioning
confidence: 98%
“…In the mouse ventricle, β-MHC, coded by myh7 , is the predominant isoform in the developing heart, then replaced by α-MHC, coded by myh6 , after birth. The myh6/myh7 ratio is important during cardiac development for the acquisition of proper cardiomyocyte mechanical performance and contraction efficiency 46 and its alteration is indicative of structural changes in the sarcomere structure and associated to fetal postnatal cardiac hypertrophy 45 , 46 . The altered expression of all these cytoskeleton components observed after ATO exposure might be involved in the impairment of the kinematic and dynamic properties, but also in reshaping cell morphology.…”
Section: Discussionmentioning
confidence: 99%